The answer and workings are in the document below. Please open it up in a new window to see it in full.
Answer:
46,100
Step-by-step explanation:
Answer:
Step-by-step explanation:
Each point of function b(x) is shifted by rule
x -----> ( x - 2 )
and
y -----> (y + 3)
( - 1.5, 0) ------> (- 3.5, 3)
(- 1, - 1) -----> ( - 3, 2)
(0, - 2) ------> ( - 2, 1)
(1, - 1) -----> ( - 1, 2)
(2, 3) -----> (0, 6)
(4, 7) -----> (2, 10)
......
Average rate of change is (f(8) - f(-6))/(8 - (-6)) = ((<span>|8 + 3| -1) - (</span><span>|-6 + 3| -1))/(8 + 6) = ((</span><span>|11| -1) - (</span><span>|-3| -1))/14 = ((11 - 1) - (3 - 1))/14 = (10 - 2)/14 = 8/14 = 4/7</span>